A Detailed Physical Explanation of an Aircraft Flutter Mechanism - Luiz Felipi Ribeiro Siqueira; Marcelo Santiago de Sousa; Flávio Luiz Cardoso-Ribeiro; Sebastião Simões da Cunha Junior (Archives of Current Research International, 2024)
Each dynamic mode (aeroelastic) is made up of torsional and rotational movements. These two movements in each mode were dissociated and the phase, amplitude, damping and frequency of each of these movements were analyzed. The structural resistances of torsion and bending, as well as the bending movement itself, have a damping effect and torsion has a destabilizing effect on the oscillations (if the centre of pressure is ahead of the flexural axis). After a certain speed, bending becomes out of phase with the applied forces. At this point, the bending has an amplifying effect on the oscillations and only the structural stiffness dampens the movement. From the speed at which the bending movement is out of phase with the applied aerodynamic loads, the damping of the mode decreases with speed, until flutter occurs. The type of analysis presented here was only possible due to the dissociation of torsion and bending movements in each mode. This is a novelty of this article. And this dissociation was made possible due to the use of the strain-based formulation, also called here as methodology NFNS_s (Non Linear Flight Dynamics – Non Linear Structural Dynamics – strain based formulation). The use of this methodology for this type of analysis was another contribution. The article presents the proposal of a new way of analyzing the aeroelastic stability of aircraft.